A Truncated Nef Peptide from SIVcpz Inhibits the Production of HIV-1 Infectious Progeny - Marcela Sabino Cunha; Thatiane Lima Sampaio; B. Matija Peterlin; Luciana Jesus da Costa (Viruses, 2016)
Nef proteins from all primate Lentiviruses, including the simian immunodeficiency virus of chimpanzees (SIVcpz), increase viral progeny infectivity. However, the function of Nef involved with the increase in viral infectivity is still not completely understood. Nonetheless, until now, studies investigating the functions of Nef from SIVcpz have been conducted in the context of the HIV-1 proviruses. In an attempt to investigate the role played by Nef during the replication cycle of an SIVcpz, a Nef-defective derivative was obtained from the SIVcpzWTGab2 clone by introducing a frame shift mutation at a unique restriction site within the nef sequence. This nef-deleted clone expresses an N-terminal 74-amino acid truncated peptide of Nef and was named SIVcpz-tNef. We found that the SIVcpz-tNef does not behave as a classic nef-deleted HIV-1 or simian immunodeficiency virus of macaques SIVmac. Markedly, SIVcpz-tNef progeny from both Hek-293T and Molt producer cells were completely non-infectious. Moreover, the loss in infectivity of SIVcpz-tNef correlated with the inhibition of Gag and GagPol processing. A marked accumulation of Gag and very low levels of reverse transcriptase were detected in viral lysates. Furthermore, these observations were reproduced once the tNef peptide was expressed in trans both in SIVcpzΔNef and HIV-1WT expressing cells, demonstrating that the truncated peptide is a dominant negative for viral processing and infectivity for both SIVcpz and HIV-1. We demonstrated that the truncated Nef peptide binds to GagPol outside the protease region and by doing so probably blocks processing of both GagPol and Gag precursors at a very early stage. This study demonstrates for the first time that naturally-occurring Nef peptides can potently block lentiviral processing and infectivity.